Immune responses and immunoprotection in crustaceans with special reference to shrimp. (17th August 2020) - Kulkarni, Amod; Krishnan, Sreedharan; Anand, Deepika; Kokkattunivarthil Uthaman, Shyam; Otta, Subhendu Kumar; Karunasagar, Indrani; Kooloth Valappil, Rajendran
Abstract: Crustacean aquaculture, dominated by shrimp, is a highly profitable food‐producing sector in the world. However, a variety of biotic and abiotic stressors can have adverse effect on the immune system of shrimp making them susceptible to diseases. Although a vertebrate‐like adaptive immune system is lacking in shrimp, an efficient innate immune system renders protection against invading pathogens. The innate immune system comprises two distinct but overlapping components, the cellular and humoral, and these are regulated through several signal transduction pathways. The signal pathways are initiated by the recognition of pathogen‐associated molecular patterns by germline‐encoded pattern recognition receptors leading to the production of different effector molecules that act against the pathogens. RNAi‐mediated post‐transcriptional gene silencing and microRNA regulation of immune response have also been found to be functional in shrimp. Similarly, apoptosis and apoptosis‐related genes are also reported, besides interferon (IFN) system‐like antiviral regulatory mechanism. Further, some form of immune memory, termed 'immune priming' or 'innate immunity with specificity' and 'quasi‐immune response' is recorded in shrimp and these abilities have been exploited in verifying the immunoprotection against different pathogens. Antigens developed either directly from the pathogens or through recombinant proteins have been tested for immune‐protective ability. RNAi‐mediated protection has also been demonstrated against different shrimp viruses. This review summarizes the available scientific information on immune responses and the immunoprotection trials carried out in crustaceans with a focus on shrimp. The available research evidences indicate the potential of developing effective immunoprophylactic measures in shrimp.